Longitudinal change in foot posture in children with cerebral palsy. (June 2017) - Church, C.; Lennon, N.; Alton, R.; Schwartz, J.; Niiler, T.; Henley, J.; Miller, F.
Purpose: Foot deformities are common in children with cerebral palsy (CP), yet the evolution of such deformities is not well documented. We aimed to observe and analyse changes in foot posture during growth in children with CP. Methods: We followed 51 children (16 unilateral, 35 bilateral; 37 Gross Motor Function Classification Scale (GMFCS) I/II, 14 III/IV) aged two to 12 years in this level II, IRB-approved prospective longitudinal study. Data after bony foot corrections were excluded. Outcome measures included coronal plane pressure index (CPPI) and pressure impulses from the heel, medial midfoot and medial forefoot. Data were LOESS smoothed and resulting models were compared for significant differences across time using a derived FANOVA method. Results: The GMFCS I/II group had more foot valgus than typically developing (TD) children until seven years which normalised thereafter. From two to 12 years, GMFCS III/IV children had more foot valgus than TD children. Heel impulse was significantly reduced in both GMFCS groups compared with TD children, and the III/IV group had less heel contact than the I/II group. Conclusions: Due to early variability and the tendency for resolving valgus foot posture in children with CP, conservative management of coronal plane foot deformity is suggested in early childhood, especially for children classified as GMFCS I and II.